2017
DOI: 10.1097/md.0000000000006405
|View full text |Cite
|
Sign up to set email alerts
|

Association between macular degeneration and mild to moderate chronic kidney disease

Abstract: Chronic kidney disease (CKD) and macular degeneration (MD) are 2 grave diseases leading to significant disability secondary to renal failure and blindness. The 2 diseases share not only common risk factors but also similar pathogenic mechanisms to renal and retinal injuries. Previous epidemiological studies indicated association between these 2 diseases. However, this concept is challenged by recent investigations. Patients with mild to moderate CKD (n = 30,696) between January 1, 1995 and December 31, 2005 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The existence of different distinct risk factors for both CKD and AMD suggests that the 2 diseases might be associated independently of the common risk factors. Moreover, several studies had identified CKD as an independent predictor of AMD after adjusting for multiple common risk factors [35][36][37][38][39]. These evidences again suggest the possibility that the 2 diseases might be independently associated.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…The existence of different distinct risk factors for both CKD and AMD suggests that the 2 diseases might be associated independently of the common risk factors. Moreover, several studies had identified CKD as an independent predictor of AMD after adjusting for multiple common risk factors [35][36][37][38][39]. These evidences again suggest the possibility that the 2 diseases might be independently associated.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, age distribution may influence the occurrence rate of AMD. Several studies included in this review enrolled participants as young as 18-25 years [36,38,39]. The inclusion of younger populations may be a factor for the variation in effect size between studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations